Synthesis and Characterization of Dimethyltin(IV) Complex with 2-Methylpyridylbenzhydrazone (AcPyBzh): Crystal Structure of [Me SnCl (AcPyBzh)] - Affan, M. A.; Ahmad, Fasihuddin B.; Hitamb, Ramli B.; Shamsuddin, Mustafa B.; Yamin, Bohari M. (Biological Sciences - PJSIR, 2005)
The reaction of dimethyltin(IV) dihalide with 2-methylpyridylbenzhydrazone (AcPyBzh) afforded the com- plex compound [Me SnCl(AcPyBzh)]. The complex was characterized by IR, 1H and 13C-1H NMR spectroscopic techniques and elemental analyses. The crystal structure of [Me SnCl(AcPyBzh)] has been determined. The AcPyBzh anion in this complex acts as a monobasic NNO bidentate ligand, the tin(IV) lying in an elongated distrorted trigonal bipyramidal environment where the azomethine nitrogen and amidate oxygen, together with the two-methyl carbons, are in the equatorial plane, whereas the chloride is the apical ligand. The crystal is monoclinic, space group P2(I)/n, with a = 12.0945 (3), b = 7.5167 (2), c = 19.9795 (4) Å, a = 90°, b = 105.85°, g = 90°.